2019
DOI: 10.1177/1747954119879348
|View full text |Cite
|
Sign up to set email alerts
|

Relative age, maturation, anthropometry and physical performance characteristics of players within an Elite Youth Football Academy

Abstract: A professional English football club with Category 1 academy status was investigated to determine the magnitude of relative age effects (RAE) within the club and explore between-quartile differences for somatic maturity, anthropometry and physical performances. Birth dates of 426 players from Under 9 to First Team were categorised into four birth quartiles (Q) and examined for relative age effects. Additionally, data on 382 players (Under 11 to First Team) were obtained for somatic maturity, anthropometry, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
(101 reference statements)
5
20
2
Order By: Relevance
“…This suggests that the small number of relatively younger players selected into this academy are considered to be highly talented, thereby facilitating their progression along the developmental pathway. On the other hand, there was a large number of Q1 players that dropout from this academy suggesting that many of these are erroneously recruited at a young age due to the relative age selection bias, which is robust within English youth football 15,[40][41][42] . Moreover, given that the prevalence of the RAE throughout this particular academy is strong 41 , it seems that the Q1 dropouts are typically being replaced by relatively older players (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the small number of relatively younger players selected into this academy are considered to be highly talented, thereby facilitating their progression along the developmental pathway. On the other hand, there was a large number of Q1 players that dropout from this academy suggesting that many of these are erroneously recruited at a young age due to the relative age selection bias, which is robust within English youth football 15,[40][41][42] . Moreover, given that the prevalence of the RAE throughout this particular academy is strong 41 , it seems that the Q1 dropouts are typically being replaced by relatively older players (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that talented youth players not favored by the RAE bias (i.e., Q3/Q4 or S2 born) may be required to demonstrate superior technical and psychological skills to endure (de)selection during academy soccer ( Cumming et al, 2018a ; Patel et al, 2019 ). Consequently, when approaching senior professional transition, these superior abilities elevate these chronologically younger players due to the diminishing physical and developmental advantages previously benefitting their chronologically older peers ( Votteler and Höner, 2014 ; Cumming et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the early stage of the talent screening campaign, the U9 participants are still far from the pre-pubertal acceleration of the development of body dimensions, which might reduce the impact of the anthropometric predictors on the soccer performance of the young people. Nevertheless, to fully understand the relationship between body size and biological maturity (Meylan et al, 2010;Lago-Peñas et al, 2011;Lovell et al, 2015;Patel et al, 2019) and soccer performance development from childhood to adolescence, more differentiated analyses would be worthwhile.…”
Section: Discussionmentioning
confidence: 99%